2016
DOI: 10.1158/1078-0432.ccr-15-1104
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CDK7, Cyclin H, and MAT1 Is Elevated in Breast Cancer and Is Prognostic in Estrogen Receptor–Positive Breast Cancer

Abstract: Purpose: CDK-activating kinase (CAK) is required for the regulation of the cell cycle and is a trimeric complex consisting of cyclin-dependent kinase 7 (CDK7), Cyclin H, and the accessory protein, MAT1. CDK7 also plays a critical role in regulating transcription, primarily by phosphorylating RNA polymerase II, as well as transcription factors such as estrogen receptor-a (ER). Deregulation of cell cycle and transcriptional control are general features of tumor cells, highlighting the potential for the use of CD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 47 publications
11
71
0
Order By: Relevance
“…Here, we observed that cyclin H was positively correlated with the increased tumor grade of ovarian cancer and the expression of the proliferation markers Ki-67 and p-CDK2. Similar results are reported by diffuse large B-cell lymphoma [27], esophageal squamous cell carcinoma [12], and breast cancer [11]. Prashant Bavi et al's study concluded that a reduced or an absent cyclin H expression was signi cantly associated with the poor overall survival of patients with diffuse large B-cell lymphoma [27].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Here, we observed that cyclin H was positively correlated with the increased tumor grade of ovarian cancer and the expression of the proliferation markers Ki-67 and p-CDK2. Similar results are reported by diffuse large B-cell lymphoma [27], esophageal squamous cell carcinoma [12], and breast cancer [11]. Prashant Bavi et al's study concluded that a reduced or an absent cyclin H expression was signi cantly associated with the poor overall survival of patients with diffuse large B-cell lymphoma [27].…”
Section: Discussionsupporting
confidence: 59%
“…Cyclin H, a member of the cyclin family, together with CDK7 and MAT1 forms the CDK-activating kinase (CAK) trimeric complex, which is necessary for the regulation of cell cycle and proliferation. Abnormal expression of cyclin H is reported in a variety of tumors such as breast cancer [11], esophageal cancer [12], endometrial cancer [13], and gastrointestinal stromal tumors [14]. However, the clinical signi cance and the biological function of cyclin H in ovarian cancer remains unclear.…”
Section: Deregulation Of Cell Cycle and Abnormal Signaling Pathways Cmentioning
confidence: 99%
“…32,33 CDK7 regulates transcription primarily by phosphorylating serine 5 at the C-terminal domain of RNA polymerase II, as well as transcription factors such as oestrogen receptor-α. 34,35 The manner in which CDK7…”
Section: Discussionmentioning
confidence: 99%
“…Numerous cancers appear to be dependent on elevated CDK7 activity to drive their oncogenic state . Because of its role in cell cycle regulation, CDK7 activity cannot be entirely de‐coupled from its broad transcriptional effects.…”
Section: Pathologies Associated With Tfiih Functionmentioning
confidence: 99%
“…Numerous cancers appear to be dependent on elevated CDK7 activity to drive their oncogenic state. 192,193 Because of its role in cell cycle regulation, CDK7 activity cannot be entirely de-coupled from its broad transcriptional effects. However, elevated expression of oncogenes is enabled by clusters of enhancers, or super-enhancers, [194][195][196] that require CDK7 activity to maintain their high-level expression.…”
Section: Cancermentioning
confidence: 99%